2020
DOI: 10.3390/polym12092059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Absorbent Foam Filling on Mechanical Behaviors of 3D-Printed Honeycombs

Abstract: Polylactic acid (PLA) hexagonal honeycomb structures were fabricated by using 3D-printing technology. By filling with absorbent polymethacrylimide (PMI) foam, a novel absorbent-foam-filled 3D-printed honeycomb was obtained. The in-plane (L- and W-direction) and out-of-plane (T-direction) compressive performances were studied experimentally and numerically. Due to absorbent PMI foam filling, the elastic modulus, compressive strength, energy absorption per unit volume, and energy absorption per unit mass of abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…That is, increases in the height-to-thickness ratio and density have an adverse impact on the specific load and specific energy absorption, resulting in a rapid decline. This is consistent with the research results of Yan et al 29 Therefore, the mechanical properties, such as the peak load and energy absorption in Figure 9(a), are analyzed below.…”
Section: Load-displacement Curve and Deformation Failure Mode Under C...supporting
confidence: 90%
See 1 more Smart Citation
“…That is, increases in the height-to-thickness ratio and density have an adverse impact on the specific load and specific energy absorption, resulting in a rapid decline. This is consistent with the research results of Yan et al 29 Therefore, the mechanical properties, such as the peak load and energy absorption in Figure 9(a), are analyzed below.…”
Section: Load-displacement Curve and Deformation Failure Mode Under C...supporting
confidence: 90%
“…There are many types of foam, such as organic foams, including polypropylene (EPP), 20 polyurethane (PU) 21,22 and graphene-reinforced PU foam, 23 and inorganic foams, including metal foam 24 and foam concrete. 25,26 For the study of mechanical properties, the finite element method has been used 27,28 to determine the effective elastic properties, and studies of the in-plane and out-of-plane compression properties 29 and quasi-static compression and dynamic impact properties 20,30 have also been performed. The results showed that the foam filling significantly improved the compressive strength, and the higher the foam density was, the greater the compressive strength and energy absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Another study on honeycomb-inspired structure is performed by using the same PLA material and FDM technology (Figure 2B). This study shows that the elastic modulus, compressive strength, and energy absorption per unit volume increase from 71.77, 2.16 MPa, 341 KJ/m 3 for the L-EH sample with low density to 496.97, 5.96 MPa, 2,132 KJ/m 3 for the L-FH-1 sample with high density (Yan et al, 2020).…”
Section: Honeycomb Structurementioning
confidence: 65%
“…The 3D printing bioinspired reinforced structures. (A) Mechanical properties of 3D printed thick honeycombs (Hedayati et al, 2016); (B) honeycomb-inspired structures and the in-plane compressive stress-strain curves for different layer thicknesses (Yan et al, 2020); (C) chiton scale-inspired flexible armor using rigid polymers (Connors et al, 2019); (D) the adult Allomyrina dichotoma beetle-inspired structure with the metal lattice structure fabricated by selective laser melting (SLM) (Du et al, 2020).…”
Section: Figure 2 |mentioning
confidence: 99%
“…To take advantage of foam materials and honeycomb, lightweight foam-filled honeycomb was proposed by a simple combination of these two components with significantly improved energy absorption capacity [ 29 ]. Therefore, the traditional hexagonal honeycomb has been widely applied in various foam-filled structures due to its advantages of a simple manufacturing process, strong impact resistance, and excellent energy absorption capacity [ 30 , 31 , 32 ]. The hexagonal honeycomb filled with foam concrete [ 33 ], expanded polypropylene foam [ 34 ], and polyurethane foam [ 35 ] were proposed, and thorough research on their mechanical performance and energy absorption was conducted.…”
Section: Introductionmentioning
confidence: 99%